1996
DOI: 10.1128/jb.178.9.2533-2538.1996
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine pyrophosphate (TPP) negatively regulates transcription of some thi genes of Salmonella typhimurium

Abstract: In Salmonella typhimurium, thiamine is a required nutrient that is synthesized de novo. Labeling studies have demonstrated probable precursors for both the 4-amino-5-hydroxymethyl-2-methylpyrimidine pyrophosphate moiety and the 4-methyl-5-(␤-hydroxyethyl) thiazole monophosphate moiety. The isolation of thiamine auxotrophs with mutations in at least five different genetic loci is reported. The majority (22 of 25) of the mutants required only the thiazole moiety of thiamine to satisfy their growth requirement. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 33 publications
3
46
0
1
Order By: Relevance
“…To determine the possible role of the thi box in gene expression, the E. coli genome was searched for the thi box sequence as detailed in Materials and Methods. Interestingly, the thi box sequence was found only in front of the three thiamin biosynthetic operons (thiCEFSGH, thiMD, and thiBPQ), whose expression in S. enterica has been shown to be negatively regulated by TPP (4,12,13). This correlation suggests that the thi box is a regulatory element involved in repression of gene expression by thiamin.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…To determine the possible role of the thi box in gene expression, the E. coli genome was searched for the thi box sequence as detailed in Materials and Methods. Interestingly, the thi box sequence was found only in front of the three thiamin biosynthetic operons (thiCEFSGH, thiMD, and thiBPQ), whose expression in S. enterica has been shown to be negatively regulated by TPP (4,12,13). This correlation suggests that the thi box is a regulatory element involved in repression of gene expression by thiamin.…”
Section: Resultsmentioning
confidence: 84%
“…However, no mutants affected in such a regulatory element have been isolated so far (10,12). Also, titration of this putative regulator by the overexpression of the untranslated RNA leader failed to reveal its presence (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research has suggested that the thiamine biosynthesis of plants is similar to that of microorganisms [24,36]. In E. coli, thiamine is synthesized by coupling HET-P (4-methyl-5-β-hydroxyethylthiazole phosphate) with HMP-PP (4-amino-5-hydroxymethylpyrimidine pyrophosphate) catalysed by ThiE (a thiamine phosphate synthase) [15,18,20,21] (Figure 1). HET-P (thiazole moiety) and HMP-PP (pyrimidine moiety) are synthesized separately under the influence of different genes [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, ThiE, a thiamine phosphate synthase, couples the two ring structures of pyrimidine and thiazole to form TP [9,[17][18][19][20] (Figure 1). Further, ThiL catalyses TP to form TPP [10,21]. In yeast, the mechanism of thiamine biosynthesis is different from prokaryotes in the precursors and the related genes [3].…”
Section: Introductionmentioning
confidence: 99%